Improved crystal quality of nonpolar a-plane GaN based on the nano pattern formed by the annealed thin Ni layer. (June 2019) - Tao, Hongchang; Xu, Shengrui; Mao, Wei; Fan, Xiaomeng; Du, Jinjuan; Peng, Ruoshi; Zhao, Ying; Li, Wen; Gao, Yuan; Zhang, Jincheng; Hao, Yue
Abstract: A method to improve the nonpolar (11–20) a -plane GaN crystalline quality is investigated. The promoted crystal quality of a -plane GaN is achieved through growing on the a -plane GaN template with nano pattern. For on-axis (11–20) plane X-ray rocking curves, the full width at half maximum values are remarkably reduced from 2834 to 1210 arcsec, 2868 to 780 arcsec along the m -axis and the c -axis directions, respectively. Also, the improved crystalline quality results in the better optical properties according to the photoluminescence and Raman measurements. Moreover, the cross-sectional transmission electron microscopy is also used to study the mechanisms of dislocation reduction. Evidently, this technique is effective in promoting crystal quality of nonpolar a -plane GaN. Highlights: A thermally annealed thin Ni film adopted in the nonpolar a -GaN growth is investigated. The crystal quality of the regrown nonpolar a -GaN epilayer is significantly improved. The regrown nonpolar a -GaN epilayer shows reduced dislocation density and enhanced optical properties.